If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -6s = 30 Solving 12 + -6s = 30 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -6s = 30 + -12 Combine like terms: 12 + -12 = 0 0 + -6s = 30 + -12 -6s = 30 + -12 Combine like terms: 30 + -12 = 18 -6s = 18 Divide each side by '-6'. s = -3 Simplifying s = -3
| 4s-2=-4+2s | | 3x-25x-x+45= | | 5x+3y=3000 | | 9000=92x(1.8)t | | y=-4*-2 | | 2ab+6bc= | | 2+(-3)+(-18)= | | (x^2-6)-(x-4)= | | 45=2v+9 | | 2f+32=94-38 | | 14.5=-16a-4(-3a-4) | | 10x^2-5xy=0 | | -14x+49=-5x+55-7x | | 3y+15=15 | | 5+25x=20x+9 | | (3+w)(2w+1)=0 | | 9x-7-2x=6-3x+7 | | 4x^3-3x^4=0.5 | | x*(x^2+2x-2.5)-5=0 | | 5(1.2-0.4y)+2y=6 | | 2x+8=6x+10 | | 3ab^2-6a^2b= | | 2a+1=5a-5 | | 4(1-2x)+5x=29 | | X^2+1x-136= | | a+b+b+80+90=180 | | 2+2x=6+1x | | 4x+2(7-x)-2x=7 | | 6(6x-6)+6=8x-6 | | -10(s+3)=-36 | | 4x-4=3+7x | | (3y-1)(8-y)=0 |